Fifty years of philosophy of religion : a select bibliography, 1955-2005 - Sanders, Andy F. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2007, ISBN: 9789004223073., 2007)
The bibliography lists about 10.000 titles of monographs, collections and articles in the field of the philosophy of religion and philosophical theology that appeared between 1955 and 2005. The majority of them are in the English language but publications in German, Dutch and French are listed as well. Though it is not claimed to be exhaustive, the bibliography offers a fairly representative survey of scholarly work on the main topics of interest. *** Publications have been systematically classified according to eleven main categories: Introductions, Surveys and Historical Issues (Part I), Religious Language (Part II), Religious Experience (Part III), Religious Epistemology (Part IV) , Theism (Part V), Hermeneutics (Part VI), Religion and Science (Part VII), Religion and Aesthetics (Part VIII), Religion and Morality (Part IX), Religious Pluralism (Part X) and Feminist Philosophy of Religion (Part XI). Part III has been subdivided into Religious Experience and Mystical Experience , Part VII into The Concept of God , (arguments for) The Existence of God , The Problem of Evil and Atheism , and Part VII into General and Historical Issues , Theological Issues and (implications of) Modern Physics, Cosmology and Biology . *** The bibliography will particularly be useful to scholars, teachers and students in the philosophy of religion, philosophical theology and systematic theology as well as to those who are interested, professionally or otherwise, in the results of academic scholarship in those fields.